Thermal profile detection through high-sensitivity fiber optic chirped Bragg grating on microstructured PMMA fiber - Sanzhar Korganbayev; Rui Min; Madina Jelbuldina; Xuehao Hu; Christophe Caucheteur; Ole Bang; Beatriz Ortega; Carlos Marques; Daniele Tosi (My University, 2018)
In this work, a linearly chirped fiber Bragg grating (CFBG) inscribed in a microstructured polymer optical fiber (mPOF) has been demonstrated for detecting temperature profiles during thermal treatments. A CFBG of 10 mm length and 0.98 nm bandwidth has been inscribed in a mPOF fiber by means of a KrF laser and uniform phase mask. The CFBG has a high temperature sensitivity of -191.4 pm/ C. The CFBG has been used as a semi-distributed temperature sensor, capable of detecting the temperature profile along the grating length, for scenarios that account minimally invasive biomedical treatments. Two experiments have been designed to validate the CFBG temperature reconstruction, using a linear gradient, and a researchgrade radiofrequency ablation (RFA) setup to apply Gaussianshaped temperature spatial profiles. The result is that the higher sensitivity of the CFBG supports the detection of spatially nonuniform temperature fields by means of spectral reconstruction.
Keywords: Chirped FBG (CFBG); distributed temperature sensor (DTS); fiber Bragg grating (FBG); optical fiber sensors; polymer optical fiber sensors; thermal ablation